Making a difference by serving in public office: Why we need more nurses in politics. Issue 8 (August 2022) - Haney, Beth
ABSTRACT: Nursing is the most trusted profession in the United States. Most nurses have the innate desire to care for others and make a difference in people's lives. Nurses are highly educated through rigorous programs that teach not only the physical sciences but also accountability, responsibility, and duty. Similarly, elected officials are accountable, have a duty to represent their constituents, and keep their best interests at the forefront of their agenda. The characteristics of nurses include higher education, integrity, responsibility, and compassion. Each one of these elements rests on the other to build a solid foundation of leadership. Nurses are natural leaders, and government needs more nurses to get involved and provide leadership benefits to our communities, including the local level where political decisions affect us all more personally. One of the responsibilities of nursing is to take an active role in politics and policy development. Nurses are a group of extraordinary individuals who are well suited to lead through elected office and influence policies that externally shape our practice and the well-being of our patients.